Unlocking the potential of flood farming to reduce flood risks and boost dryland production in Ethiopia - Desta, Gizaw; Legesse, Gizachew; Amede, Tilahun; Rooyen, Andre F. van; Whitbread, Anthony M. (CGIAR Research Program on Water, Land and Ecosystems, 2021)
Ethiopia is experiencing extreme weather variability with some areas being vulnerable to drought, while others are impacted by flooding. Despite being given relatively less attention as compared to drought, flooding has long been recognized as one of the major disasters affecting the lives and livelihoods of the people. Flood disaster has been limited in the past in terms of frequency and scope. The recent trend of increasing incidents of floods in Ethiopia is disrupting the livelihoods of the population residing in the lowlands. Flood hazard is part and parcel of living for a large number of people in the lowlands such as districts in Afar located along Awash River, in the Somali region along the Wabi Shebele River, in the South Omo along Omo River, in Gambella along the Baro and Akobo Rivers, and floodplains surrounding Lake Tana. The humid highlands that are characterized by steep ad rugged terrain and heavy rainfall features pose the lowlands prone to floods during the rainy seasons. Often, floods occur in the country as a result of intense and sustained rainfalls in the highlands causing rivers to overflow and inundate areas along the riverbanks in lowland plains. On the other hand, these regions have one of the highest potentials for flood farming as the runoff generated from the highlands of Oromia, Amhara, SNNPR, and Tigray can be available in the immediate lowlands.